Transfer pricing and tax avoidance: Moderating role of audit quality - illahi, ilham; Sumarni, Nini; Maiza, Zikrawahyuni (IAIN Surakarta, 2022)
Transfer pricing can confer advantages to companies, such as enhancing their business competitiveness and facilitating internal fund transfers. However, in practical application, companies also exploit transfer pricing for the purpose of tax avoidance, aiming to minimize their tax liabilities. Consequently, this practice has been observed to have adverse implications for the state, specifically in terms of reduced tax revenue. To explore the impact of transfer pricing on tax avoidance, researchers undertook an empirical examination. They introduced the variable of audit quality as a moderator to assess its influence on the relationship between transfer pricing and tax avoidance. The study focused on a sample of manufacturing firms listed on the Indonesia Stock Exchange, employing a purposive sampling technique. To ascertain the effects of transfer pricing variables on tax avoidance and the moderating influence of audit quality, the researchers conducted multiple linear regression tests. The findings of the study indicate a positive association between transfer pricing and tax avoidance. This research provides valuable contributions that companies engaging in transfer pricing practices are, indeed, employing them as a form of tax avoidance strategy, aiming to minimize their corporate tax obligations. However, the study does not provide evidence supporting the notion that the quality of auditors can mitigate transfer pricing undertaken for the purpose of tax avoidance.